Clinical outcomes associated with long-term exposure to airborne particulate pollution in kidney transplant recipients - Yong Chul Kim; Ejin Kim; Jiyun Jung; Jae Yoon Park; Hajeong Lee; Dong Ki Kim; Yon Su Kim; Chun Soo Lim; Jung Pyo Lee; Ho Kim (BMC, 2021)
Abstract Background Researchers have yet to investigate the specific association between 10-μm particulate matter (PM10) levels and the risk of graft failure, kidney disease, or the functional decline of transplanted kidneys, in kidney transplant recipients (KTRs). Furthermore, we know very little about the association between PM10 levels and the development of allograft rejection in transplanted kidneys. Identification of air pollution as a potential contributor to kidney disease could help reduce future disease burden, stimulate policy discussions on the importance of reducing air pollution with respect to health and disease, and increase public awareness of the hazards of air pollution. We aimed to evaluate the relationship of PM10 with the risk of graft failure, mortality, and decline of graft function in KTRs. Methods Air pollutant data were obtained from the Korean National Institute of Environmental Research. We then investigated potential associations between these data and the clinical outcomes of 1532 KTRs who underwent kidney transplantation in a tertiary hospital between 2001 and 2015. Survival models were used to evaluate the association between PM10 concentrations and the risk of death-censored graft failure (DCGF), all-cause mortality, and biopsy-proven rejection (BPR), over a median follow-up period of 6.31 years. Results The annual mean PM10 exposure after kidney transplantation was 27.1 ± 8.0 μg/m3. Based on 1-year baseline exposure, 1 μg/m3 increase in PM10 concentration was associated with an increased risk of DCGF (hazard ratio (HR): 1.049; 95% confidence interval (CI): 1.014-1.084) and BPR (HR: 1.053; 95% CI: 1.042-1.063). Fully adjusted models showed that all-cause mortality was significantly associated with 1-year average PM10 concentrations (HR, 1.09; 95% CI, 1.043 to 1.140). Conclusions Long-term PM10 exposure is significantly associated with BPR, DCGF, and all-cause mortality in KTRs.